Bacterial polysaccharides—A big source for prebiotics and therapeutics - Khan, Raees; Shah, Muhammad Dawood; Shah, Luqman; Lee, Ping-Chin; Khan, Imran (Frontiers in Nutrition, 2022)
Bacterial polysaccharides are unique due to their higher purity, hydrophilic nature, and a finer three-dimensional fibrous structure. Primarily, these polymers provide protection, support, and energy to the microorganism, however, more recently several auxiliary properties of these biopolymers have been unmasked. Microbial polysaccharides have shown therapeutic abilities against various illnesses, augmented the healing abilities of the herbal and Western medicines, improved overall health of the host, and have exerted positive impact on the growth of gut dwelling beneficial bacteria. Specifically, the review is discussing the mechanism through which bacterial polysaccharides exert anti-inflammatory, antioxidant, anti-cancer, and anti-microbial properties. In addition, they are holding promising application in the 3D printing. The review is also discussing a perspective about the metagenome-based screening of polysaccharides, their integration with other cutting-edge tools, and synthetic microbiome base intervention of polysaccharides as a strategy for prebiotic intervention. This review has collected interesting information about the bacterial polysaccharides from Google Scholar, PubMed, Scopus, and Web of Science databases. Up to our knowledge, this is the first of its kind review article that is summarizing therapeutic, prebiotics, and commercial application of bacterial polysaccharides.